Investigation of the spatial structure and interactions of the genome at sub-kilobase-pair resolution using T2C - Kolovos, Petros; Kepper, Frank Nikolaus (Nature protocols, 2018)
This protocol describes targeted chromatin capture (T2C), a high-resolution method to interrogate 3D chromatin organization and genomic interactions at sub-kilobase-pair resolution that requires minimal cell numbers and sequencing depth.
Gesehen am 16.12.2019